Baseball on Trial : The Origin of Baseball's Antitrust Exemption - Grow, Nathaniel (Book collections on Project MUSE., 2014)
The 1922 Federal Baseball Supreme Court ruling held that the 'business of base ball' was not subject to the Sherman Antitrust Act because it did not constitute interstate commerce. This work explains why the unanimous Supreme Court opinion authored by Justice Oliver Wendell Holmes, which gave rise to Major League Baseball's exemption from antitrust law, was correct given the circumstances of the time.